(untitled) (SCHOOLAR: Social and Literature Study in Education, 2022)
This study aims to find out and get information about the application of the development model of scientific-based moral mapel development to improve the character of grade X students. This study uses a Research and Development (R&D) development model consisting of the following steps: exploring potentials and problems, data collection, product design, design validation, design revision, product trials, product revisions, usage trials, product revisions, mass production. Where in the purpose of this research is to develop and explain the use of moral teaching books. on the test validator experts produced that the product is said to be valid and very feasible because it gets 76% and as much as 24% is said to be feasible and at the initial product test stage produces an A score of 11 people (55%), and at the stage of the understandingtest with 20 students after memberi response to 15 statements showed the choice of answers 75% students answered correctly. And the students who answered one as much as 25%.